## Related questions with answers

Question

Multiply algebraically. Use algebra tiles to help. m(15 - m)

Solution

VerifiedStep 1

1 of 2Use the Distributive Property: $a(b+c)=ab+ac$

$m(15-m)=m(15)-m(m)$

Use the Law of Exponent: $a^m\cdot a^n=a^{m+n}$

$=15m-m^{1+1}$

Simplify:

$=\color{#c34632}15m-m^2\color{white}\tag{1}$

## Create an account to view solutions

By signing up, you accept Quizlet's Terms of Service and Privacy Policy

## Create an account to view solutions

By signing up, you accept Quizlet's Terms of Service and Privacy Policy

## Recommended textbook solutions

## More related questions

1/4

1/7